تأثير العلاقة بين المعلم والأسرة على التفوق الدراسي للتلميذ. (دراسة ميدانية بالمدارس الابتدائية بالمقاطعة الإدارية رقم(1) بولاية بسكرة) - برجي, هناء (Changement Social; No 06 (2019): revue change social, 2019)
تهدف هذه الدراسة حسب أهميتها للكشف عن تأثير العلاقة بين المعلم والأسرة على التفوق الدراسي للتلميذ بالمرحلة الابتدائية بولاية بسكرة(الجزائر)، لما لها من تأثير كبير يمس المنظومة التعليمية بصفة عامة والتلميذ بصفة خاصة، وبالتالي الكشف عن وجود تأثير يمكن الحكم عليه بأنه تأثير ايجابي بشكل كبير، ينعكس مباشرة على التميز الدراسي، والذي يعرف بالتفوق، ولعل هذا ما تدور معالم المشكلة البحثيـة الحالية حـوله تحت سـؤال محوري مؤداه :هل تؤثر العلاقة بين المعلم والأسرة على التفوق الدراسي للتلميذ ؟ الكلمات المفتاحية : المعلم، الأسرة، التفوق الدراسي، التلميذ ا. This study aims at its importance To detect the effect of the relationship between Teacher and family to excel Of the primary school student In the state of Biskra (Algeria), because of its A significant impact affects the educational system, In general and the student in particular Thus revealing the presence of an effect Can be judged to have a positive effect Significantly, directly reflected on Academic excellence, which is known With superiority, this is perhaps what is going on The current research problem around him : Under a pivotal question Does the relationship between the teacher affect? And the family on the academic excellence For the student?   Keywords: Teacher, Family, Excellent academic, student